Neoconstructivism the new science of cognitive development - Johnson, Scott P., 1959- (New York ; Oxford : Oxford University Press, 2010)
This work brings together theoretical views that embrace computational models and developmental neurobiology, and emphasize the interplay of time, experience, and cortical architecture to explain emergent knowledge.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cognition in infants; Attention in infants; Perception in infants